2014
DOI: 10.1111/rssb.12079
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Change-Point Detection for High Dimensional Time Series via Sparsified Binary Segmentation

Abstract: Time series segmentation, a.k.a. multiple change-point detection, is a well-established problem. However, few solutions are designed specifically for high-dimensional situations. In this paper, our interest is in segmenting the second-order structure of a high-dimensional time series. In a generic step of a binary segmentation algorithm for multivariate time series, one natural solution is to combine CUSUM statistics obtained from local periodograms and cross-periodograms of the components of the input time se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
290
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(318 citation statements)
references
References 31 publications
2
290
0
Order By: Relevance
“…Similar results when the changepoints are allowed to approach one another are achieved in [17]. Recent studies include many applications and it can be found in [24][25][26][27][28][29][30][31][32]. Thus, this method is now the most understood and widely cited search algorithm used within the multiple change-point literature.…”
Section: The Binary Segmentation Methodssupporting
confidence: 59%
“…Similar results when the changepoints are allowed to approach one another are achieved in [17]. Recent studies include many applications and it can be found in [24][25][26][27][28][29][30][31][32]. Thus, this method is now the most understood and widely cited search algorithm used within the multiple change-point literature.…”
Section: The Binary Segmentation Methodssupporting
confidence: 59%
“…In these applications, the interest was in allocating an entire time series to one of a number of classes, in contrast to our goal of segmenting a time series as it evolves. Sanderson et al (2010) developed a multivariate LSW process model, which Cho and Fryzlewicz (2015) have used in segmentation of multiple locally stationary time series, while Park et al (2014) have developed estimators for the dependence structure between the multivariate time series. This multivariate LSW model could be used to extend our approach if the structure of the multiple explanatory time series is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…That paper proposes a quantum immune clonal clustering algorithm based on the change detection methods to achieve the change detection with clustering, the change detection problem of area as combinatorial optimization problem. In [13], Peijun Du conducts research on the hierarchical unsupervised change detection in multi-temporal hyperspectral images. A multi-band remote sensing image change detection method based on MRF using the MRF model integration difference change information of the image of each band.…”
Section: Literature Review and Analysismentioning
confidence: 99%